Comparison of Acoustic Parameters and Perception of Breathness and Nasality and Their Relation to the Pleasantness of Voice - Varošanec-Škarić, Gordana (Array, 1998)
This research aimed at establishing acoustic characteristics of breathy and nasal voices, in order to use these results in voice aes-thetics of voice professionals. Thirty-six trained judges evaluated degree of breathness, nasality and pleasantness of 104 male and 103 female voices. The voices were evaluated in a normal and in a rever-sed sound-order. These results were put into correlation with acous-tic variables of LTAS and then ANOVA procedure was applied and Scheo-ffe test for establishment of the significence differences. It was established that female voices showing the highest degree of breat-hness had statistically significantly 3.5 to5 kHz and in the range from 5 to 10 kHz ; and male voices had lower energy from 2.5 to 3.5 kHz and had higher energy from 5 - 10 kHz in relation to non-breathy voices. Female voices showing the highest degree of nasality have significantly higher energy from 70 to 400 Hz in a reversed sound or-der evaluation and lower energy in the part of spectrum from 1 to 1.2 kHz and from 2.5 to 5 kHz (2.5 to 3 and 3.5 to 5 kHz) in a normal so-und order, and male voices have lower energy from 330 to 550 Hz and higher energy from 850 Hz to 3 kHz in a normal sound order (significantly higher energy from 0.55 to 1 kHz, in a reversed sound order evaluation) in relation to the non-nasal voices. Also, male na-sal voices have non significantly lower energy from 3 to 10 kHz. It can also be said that nasality, more than breathness is connected with unpleasant voices.